The response to fasting and refeeding reveals functional regulation of lipoprotein lipase proteoforms - Carulla, Pere; Badia-Villanueva, Míriam; Civit, Sergi; Carrascal, Montserrat; Abian, Joaquin; Ricart-Jané, David; Llobera, Miquel; Casanovas, Albert; López-Tejero, M. Dolores (Frontiers in Physiology, 2023)
Lipoprotein lipase (LPL) is responsible for the intravascular catabolism of triglyceriderich lipoproteins and plays a central role in whole-body energy balance and lipid homeostasis. As such, LPL is subject to tissue-specific regulation in different physiological conditions, but the mechanisms of this regulation remain incompletely characterized. Previous work revealed that LPL comprises a set of proteoforms with different isoelectric points, but their regulation and functional significance have not been studied thus far. Here we studied the distribution of LPL proteoforms in different rat tissues and their regulation under physiological conditions. First, analysis by twodimensional electrophoresis and Western blot showed different patterns of LPL proteoforms (i.e., different pI or relative abundance of LPL proteoforms) in different rat tissues under basal conditions, which could be related to the tissue-specific regulation of the enzyme. Next, the comparison of LPL proteoforms from heart and brown adipose tissue between adults and 15-day-old rat pups, two conditions with minimal regulation of LPL in these tissues, yielded virtually the same tissue-specific patterns of LPL proteoforms. In contrast, the pronounced down-regulation of LPL activity observed in white adipose tissue during fasting is accompanied by a prominent reconfiguration of the LPL proteoform pattern. Furthermore, refeeding reverts this down-regulation of LPL activity and restores the pattern of LPL proteoforms in this tissue. Importantly, this reversible proteoform-specific regulation during fasting and refeeding indicates that LPL proteoforms are functionally diverse. Further investigation of potential differences in the functional properties of LPL proteoforms showed that all proteoforms exhibit lipolytic activity and have similar heparin-binding affinity, although other functional aspects remain to be investigated. Overall, this study demonstrates the ubiquity, differential distribution and specific regulation of LPL proteoforms in rat tissues and underscores the need to consider the existence of LPL proteoforms for a complete understanding of LPL regulation under physiological conditions.